2016
DOI: 10.4103/0974-620x.176099
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, knowledge, and barriers to low vision services among eye care practitioners

Abstract: Background:Eyesight plays an important role in our day today life. When the vision gets hampered, daily activities of an individual will be affected. The prevalence of visual impairment is increasing across the globe, with more burdens on the developing world. The uptake of low vision services remains to be low in developing countries like India.Methods:A newly constructed questionnaire using information from previously conducted telephonic interviews and article search was administered among 50 eye care pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 17 publications
4
12
0
Order By: Relevance
“…ECPs’ perception and patients’ perception were considered to be an important obstacle in accessing the LVC services by Matti et al ,[7] which is coherent with the current study where ECP's perceived factors like gender, literacy, and low socio-economic status of the patients had influence on the referral. Lack of awareness on available services of LVC was also found to be a barrier among ECPs which correlates with Jose et al [6] Barriers among patients were lack of awareness about the services, compromising the visual demand, and non-referral to LVC services, which was similar to previous studies. [36715] Non-availability of the low vision devices was found to be a barrier in previous studies,[36] but in our study it was not found to be a barrier.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…ECPs’ perception and patients’ perception were considered to be an important obstacle in accessing the LVC services by Matti et al ,[7] which is coherent with the current study where ECP's perceived factors like gender, literacy, and low socio-economic status of the patients had influence on the referral. Lack of awareness on available services of LVC was also found to be a barrier among ECPs which correlates with Jose et al [6] Barriers among patients were lack of awareness about the services, compromising the visual demand, and non-referral to LVC services, which was similar to previous studies. [36715] Non-availability of the low vision devices was found to be a barrier in previous studies,[36] but in our study it was not found to be a barrier.…”
Section: Discussionsupporting
confidence: 85%
“…Lack of awareness on available services of LVC was also found to be a barrier among ECPs which correlates with Jose et al [6] Barriers among patients were lack of awareness about the services, compromising the visual demand, and non-referral to LVC services, which was similar to previous studies. [36715] Non-availability of the low vision devices was found to be a barrier in previous studies,[36] but in our study it was not found to be a barrier. Unlike previous studies, this study does not represent language or medical comorbidities as a barrier.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Most common barriers reported are external to the practitioners themselves and have also been mentioned in other studies. 11 , 12 , 13 These results have implications for planning and implementing low vision services in these regions.…”
Section: Discussionmentioning
confidence: 94%
“…The design of the questionnaire was based on the review of relevant literature. 9 , 11 , 12 , 13 The survey was preceded by a pilot study conducted among eye care professionals who did not take part in the final study in order to critically evaluate and finalise the questionnaire. All queries from the questionnaire during the pilot study were addressed and the questionnaire adjusted accordingly before the final study was conducted.…”
Section: Methodsmentioning
confidence: 99%